2009
DOI: 10.1177/1471301208099048
|View full text |Cite
|
Sign up to set email alerts
|

African American caregivers

Abstract: Despite the significance of an early diagnosis of Alzheimer's disease (AD), African Americans are diagnosed in later stages of the disease and present with greater cognitive impairment at the time of diagnosis when compared to Euro-Americans. To this end, there exists a paucity of research on diagnostic pathways among African Americans with dementia. More specifically, few studies have explored help-seeking pathways from the initial manifestation of symptoms until an actual diagnosis of Alzheimer's disease was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
(63 reference statements)
0
24
0
Order By: Relevance
“…Full demographic characteristics of participants were not reported in all studies, but most carers were female and either spouses or adult children. Eleven studies sought the perspectives of specific ethnic groups: two Hispanic and Latino communities within the United States of America (USA) (Neary and Mahoney, 2005;Ortiz and Fitten, 2000), four African American communities (Clark et al, 2005;Cloutterbuck and Mahoney, 2003;Hughes et al, 2009;Jackson, 2016), three Chinese communities in the USA (Zhan, 2004), Canada (Koehn et al, 2012), and China (Yan et al, 2017), one of South Asian Canadians (McCleary et al, 2012), and one UK study which purposively sampled South Asian, Black African or Caribbean, Asian, White, and Chinese carers (Mukadam et al, 2011a). Study quality was variable and the results of the appraisal can be found in Table 4.…”
Section: Study Characteristics and Quality Appraisalmentioning
confidence: 99%
“…Full demographic characteristics of participants were not reported in all studies, but most carers were female and either spouses or adult children. Eleven studies sought the perspectives of specific ethnic groups: two Hispanic and Latino communities within the United States of America (USA) (Neary and Mahoney, 2005;Ortiz and Fitten, 2000), four African American communities (Clark et al, 2005;Cloutterbuck and Mahoney, 2003;Hughes et al, 2009;Jackson, 2016), three Chinese communities in the USA (Zhan, 2004), Canada (Koehn et al, 2012), and China (Yan et al, 2017), one of South Asian Canadians (McCleary et al, 2012), and one UK study which purposively sampled South Asian, Black African or Caribbean, Asian, White, and Chinese carers (Mukadam et al, 2011a). Study quality was variable and the results of the appraisal can be found in Table 4.…”
Section: Study Characteristics and Quality Appraisalmentioning
confidence: 99%
“…However, relatively few studies have investigated memory failure attribution and help-seeking behaviors in this group. By investigating projected help-seeking behaviors and memory failure attribution in a pre-morbid sample including a large African American group, the present study begins to address this gap in the literature and shed light on some of the mechanisms at play in the consistent discrepancies observed between African Americans and non-Hispanic Whites when it comes to stage of diagnosis and timely treatment (Cloutterbuck & Mahoney, 2003;Hughes et al, 2009). The fact that personal exposure to AD is more salient to African Americans when considering the causes of their own memory failures highlights the great value these individuals place on personal experience and family ties.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cloutterbuck and Mahoney (2003) noted that the caregivers of African Americans with dementia deemed their interactions as generally negative, as providers often "dismissed" and "devalued" their expressed concerns. Similarly, Hughes, Tyler, Danner, and Carter (2009) found that family caregivers of African American patients frequently felt that their concerns surrounding memory loss were overlooked, as physicians instead focused their assessments on other chronic disorders that prominently affect the African American community, as opposed to carrying out memory assessments. In turn, Hughes et al (2009) suggest that this could play a role in the initial misdiagnoses of African American patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, African-Americans have a higher rate of vascular disease such as T2DM, a condition thought to increase brain dysfunction in higher cortical abilities. Despite the significance of an early diagnosis of Alzheimer's disease (AD), African Americans are diagnosed in later stages of the disease, demonstrate greater cognitive impairment at the time of diagnosis, and receive less adequate treatment following diagnosis (Hughes, Tyler et al 2009;Chin, Negash et al 2011). As the major public health emphasis for African Americans remains focused around physical disease (e.g., heart disease, lower limb amputations, and kidney disease), there is growing concern that health care professional and the patients for whom they provide care may be missing opportunities for connecting integrative mind-body health.…”
Section: Public Health Implications Of Dementia Related Healthmentioning
confidence: 99%